Effect of Tetramethylpyrazine on Atherosclerosis and SCAP/SREBP-1c Signaling Pathway in ApoE−/− Mice Fed with a High-Fat Diet. (12th April 2017) - Zhang, Ying; Ren, Pan; Kang, Qunfu; Liu, Weihong; Li, Sinai; Li, Ping; Liu, Hongxu; Shang, Juju; Zhang, Lei; Gong, Yanbing; Zhou, Mingxue
Abstract : Lipid metabolism dysregulation plays a crucial role in the occurrence of atherosclerosis (As). SCAP/SREBP signaling is the main pathway for regulating lipid metabolism. Tetramethylpyrazine (TMP), a Traditional Chinese Medicine (TCM) for treating angina pectoris, has antiatherosclerotic effects and ameliorates blood lipids disturbance. However, its precise mechanism remains unclear. This study investigated the mechanism of TMP in ameliorating As in mice model. After six weeks of high-fat diet, 30 ApoE −/− mice were randomized (n = 10 ) and treated with Lipitor, TMP, or distilled water for six weeks. The serum blood lipids and insulin levels were measured. The expressions of PAQR3, Insig-1, SCAP, SREBP-1c, IRS-1, PI3K, Akt, and mTORC-1 in the adipose tissues were determined. The results showed that TMP could significantly decrease blood lipids levels, insulin, and corrected plaque area of the ApoE −/− mice as compared to the untreated mice (P < 0.05, P < 0.01 ). Moreover, TMP could significantly downregulate the expressions of SCAP, SREBP-1c, PAQR3, IRS-1, PI3K, Akt, and mTORC1 (P < 0.01 ). Thus, TMP may ameliorate lipid metabolism disorder and As by downregulating PAQR3 and inhibiting SCAP/SREBP-1c signaling pathway. In addition, PI3K/Akt/mTORC1 signaling pathway may be involved in this process.